The Swedish national guidelines on penile cancer - Gerdtsson, Axel; Abedi, Eliya; Baseckas, Gediminas; Brorson, Håkan ; 0000-0001-9968-6062; Dorofte, Luiza; Fall, Sofia; Filipsson, Emelie; Forssell, Johan; Glombik, Dominik; Grelaud, Diane ; 0000-0001-8425-5833; Hellman, Fatou; Jakobsson, Anna Karin; et al. (Scandinavian Journal of Urology, 2025)
Objective: The Swedish national guidelines on penile cancer were first published in 2013. The objective of this study is to present the 2023 update of these guidelines and highlight the differences to the European Association of Urology (EAU) / American Association of Clinical Oncology (ASCO) guidelines on penile cancer. Material and methods: A review of the literature and a comparison to the EAU / ASCO guideline on penile cancer was performed. Differences between the EAU / ASCO guidelines and the Swedish national guidelines are highlighted. Results: The Swedish national guidelines on penile cancer emphasized the consultation of a national multidisciplinary treatment conference for all patients diagnosed with both primary and recurrent penile cancer or penile intraepithelial neoplasia (PeIN). Clinically lymph node negative patients diagnosed with >pT1G1 are offered dynamic sentinel node biopsy (DSNB). In the EAU / ASCO guidelines the DSNB is optional for T1aG2 patients. Penile cancer surgery is centralized to two hospitals. Perioperative chemotherapy is offered to patients with ≥N2. In the EAU / ASCO guidelines the use of perioperative chemotherapy for N2 patients is optional. A structured follow-up program is advocated to find recurrences at an early stage. Conclusions: The Swedish national guidelines on penile cancer have been updated and compared to the EAU / ASCO guidelines. The national multidisciplinary treatment conference, centralization of surgery, the use of perioperative chemotherapy and a structured follow-up are the cornerstones of the Swedish national guidelines on penile cancer.
Publisher Copyright: © 2025 The Author(s). Published by MJS Publishing on behalf of Acta Chirurgica Scandinavica..
Keywords: Follow-up; guidelines; lymph node dissection; penile cancer; penile intraepithelial neoplasia